Trust, Financial Literacy and Investment Intention: A Case in Securities Crowdfunding Platform using Trust Transfer Theory - Ulfa Nahdhiroh; Mega Noerman Ningtyas (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
This study aims to reveal the role of trust in mediating the effect of financial literacy on investment intentions on the securities crowdfunding platform. The research method used is quantitative with a survey approach, using purposive sampling technique, with a total of 180 investors. Data were analyzed using Partial Least Squares (PLS-SEM). The results showed that financial literacy significantly affects investment intention and trust in the securities crowdfunding platform. In addition, trust in the platform also plays an important role in increasing trust in the fundraiser. This study concludes that financial literacy and trust in the platform have a significant impact on investors' intention to invest, and support the application of Trust Transfer Theory in the context of securities crowdfunding.